Kualitas Pelayanan Mitra Gojek Terhadap Kepuasan Pengguna Layanan Go-Ride - Jagomos C Jansela Situmorang; Fauzi Akbar Maulana Hutabarat; Wong Pong Lan; Ngajudin Nugroho; Lisa (ARBITRASE: Journal of Economics and Accounting, 2021)
This study aims to analyze whether there is an effect of service quality on Gojek customer satisfaction. In this case the author conducted research at the Medan Cendana Polytechnic, with a sample population of 130 students of Medan Cendana Polytechnic. The sampling technique used is by distributing questionnaires via google form to 130 respondents. The results in this study indicate that service quality has a positive and significant effect on customer satisfaction. This is evidenced by the results of the t-test, that the significance value is 0.000 <0.05 and the tcount is 14,274 > ttable1,656. As for the results of the coefficient of determination that the effect of service quality on customer satisfaction is 61.1% and the remaining 38.9% is influenced by other factors.